Comparison of N and S Doped TiO2 Electrode for Dye Sensitized Solar Cells - Wang, S.; Yu, Z.C.; Han, L.; Dai, C.L.; Song, J.Y. (Asian Journal of Chemistry, 2011)
Doped TiO2 semiconductor thin films were synthesized using N and S as photovoltaic propertyenhancing impurities by micro-plasma oxidation method. The influence of the doping ions on the structural and microstructure of the TiO2 films were investigated by X-ray diffraction, scanning electron microscopy and electrical impedance spectra. The results show that the dye-sensitized solar cell efficiency fabricated with doped TiO2 is remarkably better than that of undoped TiO2. Also, the performance of N-doped TiO2 electrode is better than that of S-doped TiO2 electrode in terms of Voc, short circuit current density (Jsc) and power conversion efficiency. These phenomena were related to the surface area, crystalline structures and charge transfer kinetics modifications induced by non-metal-ion dopants.